CANADIAN PEDIATRICIANS' VIEWS AND KNOWLEDGE ABOUT CANNABIS USE FOR MEDICAL PURPOSES AMONG CHILDREN AND ADOLESCENTS. (18th May 2018) - Belanger, Richard; Grant, Christina; Côté, Myriam; Donner, Elizabeth; Breakey, Vicky; Laflamme, Julie; Pinard, Anne-Marie; Rieder, Michael
Abstract: BACKGROUND: Cannabis use for medical purposes has gathered growing interest from the public through its purported benefits. Since 2001, Health Canada has authorized availability from health practitioners, even for paediatric patients, despite concerns regarding efficacy and adverse effects among children and adolescents. It is likely that a lack of knowledge regarding the substance and indications for use, tempered by known and unknown side effects, dictate paediatricians' practice toward cannabis. OBJECTIVES: This study examines the views and knowledge of Canadian paediatricians regarding the use of cannabis for medical purposes among children and adolescents. Differences between general paediatricians and sub-specialists were explored. DESIGN/METHODS: Data was collected using a Canadian Paediatric Surveillance Program (CPSP) one-time survey performed in 2017. A total of 864 paediatric physicians (33% participation rate) were asked about medical use of cannabis. They were also asked personal and professional characteristics. Descriptive statistics regarding their views and knowledge towards cannabis use for medical purposes are reported, as well as significant differences (p<0.05) based on their belonging to either the general paediatricians or the sub-specialists subgroup. RESULTS: General paediatricians represented 55.4% of the analyzed sample, with 36.7% having ≥ 20 years of practice. Half (50.4%) of all surveyed paediatricians had encountered in the past year patients who used cannabis for medical purposes (authorized or not). Half (50.6%) were also aware that Canadian physicians could authorize cannabis to children for medical purposes. More (61.3%) knew they could authorize it to adolescents (significantly more among sub-specialists, p=0.03). Nearly half (46.5%) believed that there are appropriate indications to support the authorization of cannabis for medical reasons to the paediatric population (significantly more among sub-specialists, p<0.01). The most common reasons for not prescribing were the lack of medical evidence about clinical efficacy (82.8%), dosing/toxicity (79.0%) and concerns about potential long-term impacts (78.4%). Most paediatricians reported little knowledge on why cannabis could be authorized (75.9%), what products may be authorized (89.1%), and how cannabis can be authorized (90.4%), sub-specialists reporting the highest knowledge on each topic (p<0.01). CONCLUSION: Cannabis use for medical purposes is a situation frequently encountered by paediatricians. While they are generally supportive of certain medical indications for its authorization, most have minimal knowledge on its use and, report concerns about efficacy and safety. Differences between general paediatricians and sub-specialists probably emerge from conditions treated by these two groups. Our study highlights the need for timely continuing education for all paediatricians on this topic.